On the Issue of the Succession Law Reform in Russia and the European Union: Some Results of 2017 – 2019 - PUKHART, Alexandr А.; AFGANOGLY, Hajiyev Adil (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019DO - 10.14505//jarle.v10.3(41).23, 2019)
The authors investigate the features of reforming the succession law in Russia and the European Union. It was revealed that: (1) the topic of cross-border succession  is becoming increasingly important in Europe, given that substantive laws in EU Member States vary significantly with respect to the form of will, the admissibility of succession  agreements, the rules of calling for inheritance, etc.; (2) these problems should have been adopted by Regulation No. 650/2012 on succession  adopted on July 4, 2012, which has been applied in all EU member states since August 17, 2015; (3) The Regulation introduced the European Certificate of Succession (ECS) - a document that must be recognized in all member states without any special procedure; (4) on the one hand, ECS has simplified the procedure for accepting and registering an inheritance; on the other hand, problems have been identified that arise as a result of applying the laws of individual states; (5) the reform of the Russian legislation on inheritance, which took place in 2017-2019, was aimed at ensuring the interests of heirs by introducing such institutions as: succession fund, succession agreement, joint testament of spouses; which made it possible to conclude that Russian legislation is increasingly intensively keeping up with the times and becoming more flexible in terms of inheritance.